Can Monetary Reward Modulate Social Attention? - Lo Gerfo, Emanuele; De Angelis, Jacopo; Vergallito, Alessandra; Bossi, Francesco; Romero Lauro, Leonor Josefina; Ricciardelli, Paola (Frontiers in Psychology, 2018)
Selective visual attention is a primary cognitive function, which allows the selection of the most relevant stimuli in the environment by prioritizing their processing. Several studies showed that this process can be influenced by both social signals, as gaze direction (i.e. the Gaze Cueing Effect, GCE) and by the motivational valence of gratifying stimuli, such as monetary rewards. The aim of this study was to explore whether GCE could be modulated by a monetary reward. To this end, were created two experiments: the first in which two sessions of the traditional Gaze cuing task took place before and after participants run a modified version of the Dictator game in order to obtain monetary reward; the second as control experiment, in which instead of the Dictator game participants performed a perceptual task, which did not include any reward. Results supported previous findings showing the presence of the GCE, i.e. faster responses when the target appeared in the gazed-at location. Interestingly, results did not reveal significant differences among the groups. Therefore, contrarily to what was observed by previous attentional orienting studies with non-social stimuli, monetary reward did not modulate (or interfere with) the orienting of attention mediated by gaze direction as measured by the GCE. Taken together our results suggested that social signals such as gaze direction have a greater impact than monetary reward in orienting selective attention.